2017
DOI: 10.1186/s12974-017-0807-8
|View full text |Cite
|
Sign up to set email alerts
|

The potential neuroprotective role of a histone deacetylase inhibitor, sodium butyrate, after neonatal hypoxia-ischemia

Abstract: BackgroundHistone deacetylase inhibitor (HDACi), sodium butyrate (SB), has been shown to be neuroprotective in adult brain injury models. Potential explanation for the inhibitor action involves among others reduced inflammation. We therefore anticipated that SB will provide a suitable option for brain injury in immature animals. The aim of our study was to test the hypothesis that one of the mechanisms of protection afforded by SB after neonatal hypoxia-ischemia is associated with anti-inflammatory action. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 79 publications
4
48
1
Order By: Relevance
“…10 Interestingly, H19 regulates the expression of several HDACs. 11,12 In addition, the HDAC inhibitor sodium butyrate shifts microglia to a neuroprotective phenotype in an experimental model of ischemic stroke, 13 which could serve as a point of therapeutic intervention. We considered whether H19 participates in the phenotypic changes of microglia through regulation of HDACs during ischemic stroke and if H19 could serve as a biomarker for stroke in humans.…”
Section: Strokementioning
confidence: 99%
“…10 Interestingly, H19 regulates the expression of several HDACs. 11,12 In addition, the HDAC inhibitor sodium butyrate shifts microglia to a neuroprotective phenotype in an experimental model of ischemic stroke, 13 which could serve as a point of therapeutic intervention. We considered whether H19 participates in the phenotypic changes of microglia through regulation of HDACs during ischemic stroke and if H19 could serve as a biomarker for stroke in humans.…”
Section: Strokementioning
confidence: 99%
“…Butyrate reportedly exerts numerous beneficial effects on the gut, immune system, central nervous system, and cardiovascular system [21]. Previous studies have shown that butyrate has a positive effect on both astrocytes [22] and microglia [23][24][25][26] of the central nervous system. Moreover, previous research in our laboratory shows that β-hydroxybutyric acid as a short-chain fatty acid, the same with butyrate, protected dopaminergic neurons through inhibiting microglia-mediated neuroinflammation both in vitro and in vivo [27] and limited the excessive activation of microglia and inhibited the production of inflammatory cytokines Figure 3: NaB attenuates Aβ toxicity and maintains mitochondrial respiratory function in N2a cells.…”
Section: Discussionmentioning
confidence: 99%
“…Cells. Aβ [25][26][27][28][29][30][31][32][33][34][35] (synthesized by Shanghai Sangon Biological Engineering Technology & Services Co.) was diluted in distilled water at a concentration of 16 mmol/L and was maintained at 37°C for 7 days to preage the peptide. N2a cells were divided into four groups: the control (NT) group, the NaB (2 mM) group, the Aβ 25-35 (40 μmol/L) treatment group, and the Aβ 25-35 (40 μmol/L) with NaB (2 mM) pretreatment group.…”
Section: Treatment Of N2amentioning
confidence: 99%
See 2 more Smart Citations